Participative Decision-Making in a Consultative Committee Context - Warner, Malcolm (Relations industrielles / Industrial Relations, 1974)
This paper attempts to look at consultative participation, in a British setting, of bodies on which trade union « representatives  » sit at the national level, together with committee members from other industrial interest-groups, government departments and independents.